2016
DOI: 10.17795/zjrms-7366
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Effects of Artemisia deserti Ethanolic Extract and Diazinon on Male Rat Kidney

Abstract: Background: Artemisia is a diverse genus of Asteraceae family that has pharmacological effects such as antiinflammatory, anticancer, antidiabetic and is used for treatment of diseases, including antioxidant effects against oxidative stress. Objectives: This study investigated the antioxidant effects of Artemisia deserti Krasch extract and diazinon. Materials and Methods: In this experimental study, Artemisia deserti was collected from Isfahan, Iran then 20 g of flower powder was extracted with 150 mL 80% ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…The extract produced histopathological alterations in the kidney of rats. The serum carbamide level was elevated, but the change was not significant [110]. Similarly to our study, levels of urea were increased significantly and kidney tissue damage was observed in the treated groups compared to control group in the experiment of Ene-ojo et al .…”
Section: Discussionsupporting
confidence: 82%
“…The extract produced histopathological alterations in the kidney of rats. The serum carbamide level was elevated, but the change was not significant [110]. Similarly to our study, levels of urea were increased significantly and kidney tissue damage was observed in the treated groups compared to control group in the experiment of Ene-ojo et al .…”
Section: Discussionsupporting
confidence: 82%
“… Note . References are numbered as follows: 1 (Megdiche‐Ksouri et al, ), 2 (Ascensäo & Pais, ), 3 (Naili, Alghazeer, Saleh, & Al‐Najjar, ), 4 (Al‐Snafi, ), 5 (Lellau & Liebezeit, ), 6 (Charkhpour, Delazar, Mohammadi, Gholikhani, & Parvizpur, ), 7 (Willaman & Schubert, ), 8 (Kinney & Sugihara, ), 9 (Rätsch, ), 10 (Ahameethunisa & Hopper, ), 11 (Pradeep & Rengaswamy, ), 12 (Arokiyaraj et al, ), 13 (Judžentienė & Buzelytė, ), 14 (Haniya & Padma, ), 15 (Pires, Fulvio, Negri, Duarte‐Almeida, & Elisaldo, ), 16 (Ikram et al, ), 17 (Bhakuni, Jain, Sharma, & Kumar, ), 18 (Suresh, Ahuja, Paramakrishnan, & Sebastian, ), 19 (Feyera, Terefe, & Shibeshi, ), 20 (Lone, Bhat, & Khuroo, ), 21 (Sivagnanam, Rao, Mudiganti, & Jeelani, ), 22 (Wright, ), 23 (Suresh et al, ), 24 (Heo et al, ), 25 (Ruwali, Ambwani, Gautam, & Thapliyal, ), 26 (Corsi & Nencioni, ), 27 (Pala, Shukla, Alok, Kudale, & Desai, ), 28 (Kim, Adesogan, & Ko, ), 29 (Ali, Shah, & Shah, ), 30 (Choi, Kang, & Kim, ), 31 (Kim et al, ), 32 (Kristiani et al, ), 33 (Salhi et al, ), 34 (Aynehchi, Salehi Sormaghi, Amin, Khoshkhow, & Shabani, ), 35 (Fazly Bazzaz, Haririzadeh, Imami, & Rashed, ), 36 (Kapustina et al, ), 37 (Darwish‐Sayed, El‐Shamy, Hassan, & El‐Shahrawy, ), 38 (Pirbalouti, Firoz nezhad, Craker, & Akbarzadeh, ), 39 (Ene, Atawodi, Ameh, Kwanashie, & Agomo, ), 40 (Yan et al, ), 41 (Khatoon, ), 42 (Aynehchi et al, ), 43 (Noori, Amjad, & Yazdani, ), 44 (Elsharkawy & Shiboob, ), and 45 (Goodson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Kidneys often face the problem of toxicity if the human body were extremely exposed to anti-nutritional substances (Morgado & Neves, 2012;Tomino, 2014). As a consequence, the possibility of pathological changes is immensely high (Noori et al, 2013). The kidney damage also was determined by histological examination of kidney tissue.…”
Section: Introductionmentioning
confidence: 99%